Development of a Recombinase Polymerase Amplification Fluorescence Assay for the Detection of Canine Adenovirus 2 - Xiao, Li; Zhang, Mengdi; Tian, Zhige; Ge, Ye; Zhang, Tongyuan; Yi, Li; Cong, Feng (Frontiers in Veterinary Science, 2021)
Canine adenovirus type 2 (CAdV-2), which often coinfected with other pathogens causing the canine infectious respiratory disease (CIRD). Rapid, efficient and convenient pathogen detection is the best approach for early confirmatory diagnosis. In this study, we developed and evaluated a rapid real-time recombinase polymerase amplification (RPA) assay for detection of canine adenovirus 2 (CAV), which can detect CAV within 15 min at 39°C. The detection limit of that assay was 214 copies/μL DNA molecules per reaction. The specificity was indicated by a lack of cross-reaction with canine distemper virus (CDV), canine coronavirus (CCV) and canine parvovirus (CPV). Field and clinical applicability of this assay were evaluated using 86 field samples. The coincidence rate of the detection results for clinical samples between CAV-RPA and qPCR was 97.7%. In summary, the real-time CAV-RPA analysis provides an efficient, rapid and sensitive detection method for CAV.